Evaluasi Tatakelola TI Menggunakan Framework COBIT 2019 dan Capability Maturity Model Integration (CMMI) - M. Dwi Aulia Akbar; Erwin Setiawan Panjaitan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The State Islamic University of North Sumatra (UIN-SU) Medan has the responsibility for the management and security of information technology (IT). However, the results of an interview with the Head of PUSTIPADA UIN-SU Medan revealed several problems, such as lack of strategic planning, absence of long-term vision, limited resources, lack of competent staff in IT management, and no audits have been conducted. To overcome these problems, an evaluation of IT governance capabilities was conducted using the COBIT 2019 framework and Capability Maturity Model Integration (CMMI) to measure the level of organizational maturity. The results showed that the priority domain MEA03 (Managed Compliance with External Requirements) obtained a score of 100. Based on CMMI, the MEA03 domain reached a maturity level of 100% and was at the Fully Achieved capability level (85–100%). Thus, the capability level objective process MEA03 has reached level 5 and the audit status is declared achieved.